1987
DOI: 10.1073/pnas.84.11.3802
|View full text |Cite
|
Sign up to set email alerts
|

Induction of murine interleukin 1: stimuli and responsive primary cells.

Abstract: An interleukin 1a (IL-1a) cDNA probe and an IL-l responsive T-cell clone (D1O.G4; half-maximal stimulation, 0.1-1 pM) have been used to study the production of IL-1 by primary murine cell populations, particularly macrophages and dendritic cells. Spleen and peritoneal macrophages produced IL-1 mRNA and released biologically active IL-1 when challenged with lipopolysaccharide (LPS). Induction of IL-1 was evident over a dose range of 0.01-10 ,jg of LPS per ml, and maxmal mRNA levels were maintained from 4 to 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…In contrast, other studies have shown that macrophages can increase the sensitivity of MLR to Peyer's patch cells [27]. It is most likely that this effect may be mediated by macrophages production of IL-1 which is not produced by DC [16], but which amplifies DC function [15] and all these factors require further experimental analysis. Although it has been reported in previous studies that an allogeneic MLR can occur without the involvement of IL-1 [23], it is likely that all T cell responses require a number of co-stimulatory factors [11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, other studies have shown that macrophages can increase the sensitivity of MLR to Peyer's patch cells [27]. It is most likely that this effect may be mediated by macrophages production of IL-1 which is not produced by DC [16], but which amplifies DC function [15] and all these factors require further experimental analysis. Although it has been reported in previous studies that an allogeneic MLR can occur without the involvement of IL-1 [23], it is likely that all T cell responses require a number of co-stimulatory factors [11].…”
Section: Discussionmentioning
confidence: 89%
“…Variations in levels of cytokine production in the epidermis and the intestine may account for the differences in maturity of DC at the two sites. Both IL-1 and GM-CSF, which have been reported to amplify DC function [15] are produced by cells of the human intestinal tissues [30], but levels have not been compared with those of the epidermis. Peritoneal cavity macrophage derived-DC from p30 transgenic mice demonstrated greater allogeneic MLR stimulatory activity when incubated with T cells from inbred BALB/c mice at all three responder:stimulator ratios and time points.…”
Section: Discussionmentioning
confidence: 99%
“…Highly purified splenic B or T cells do not produce stL-1 in response to stimulation with iscoms, while peritoneal cells produce IL-1 upon iscom treatment in vivo (manuscript in preparation). The production of IL-1 in LPS or cholera toxin-stimulated murine cells is mediated by macrophages [7,27], and the production of IL-1 by peritoneal macrophages, cultured with heat-killed bacteria as antigen, was enhanced by addition of T cell products [28].…”
Section: Discussionmentioning
confidence: 99%
“…Activity of immunostimulants for innate immunity has been evaluated based on the induction of cytokine production and phagocytosis by mammalian macrophages (28,29). Because LPS from Gram-negative bacteria are active in these assays at extremely low concentrations, the effects of LPS derived from contaminated bacteria in samples is a serious problem for evaluating immunostimulation.…”
Section: Therapeutic Effect Of Ge-3 Against Viral Infectionmentioning
confidence: 99%